Knowledge, attitude, and practice toward seasonal influenza vaccine during the COVID-19 pandemic among students at King Saud bin Abdulaziz University for Health Sciences-Jeddah, Saudi Arabia - Amir Abushouk; Mohamed Eldigire Ahmed; Zaher Althagafi; Abdulrhman Almehmadi; Samer Alasmari; Fares Alenezi; Muhannad Fallata; Rayan Alshamrani (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Annual influenza vaccine is recommended among health professionals especially, health science undergraduates; although, studies suggest that there is a low level of vaccine coverage among health care undergraduates. Thus, the study aimed to investigate students' knowledge, attitudes, and practices regarding the seasonal influenza vaccine at King Saud bin Abdulaziz University for Health Sciences (KSAU-HS) in Jeddah, Saudi Arabia. METHODS: A cross-sectional, unicentral study was carried out during the period of April to November 2021. A total of 341 validated questionnaires that included four sections were distributed in all four different colleges of KSAU-HS. Data management and analyses were carried out using Statistical Software for Social Sciences (SPSS) version 25. RESULTS: Out of 341 respondents, 336 participants completed the full survey (98.53% completion rate). The majority of participants were males (67.6% and the most participants were from the college of medicine (60.4%). The mean knowledge score of students was found to be (11.3 ± 2.0) out of 14 points. The most common barrier to vaccination among healthcare students was not having enough time to take the vaccine (23.8%), while the second one was the COVID-19 pandemic (22.32%). The vaccination rate in 2020 was 103 (30.7%), while 235 (80.4%) students stated that they have received the vaccine previously. School/work requirements and the student's awareness of the vaccine's importance were the most common reasons for taking the influenza vaccine. CONCLUSION: Even though students showed a high level of knowledge and a positive attitude towards the influenza vaccine, they generally had a low level of vaccine uptake. To enhance immunization rates, we encourage vaccine campaigns in all healthcare colleges. Further studies are needed to identify influences on students' attitudes and practices regarding influenza vaccination.